2013
DOI: 10.1128/mbio.00460-13
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Vaginal Bacteria andd- andl-Lactic Acid Isomers on Vaginal Extracellular Matrix Metalloproteinase Inducer: Implications for Protection against Upper Genital Tract Infections

Abstract: We evaluated levels of vaginal extracellular matrix metalloproteinase inducer (EMMPRIN) and matrix metalloproteinase (MMP-8) in vaginal secretions in relation to the composition of vaginal bacterial communities and d- and l-lactic acid levels. The composition of vaginal bacterial communities in 46 women was determined by pyrosequencing the V1 to V3 region of 16S rRNA genes. Lactobacilli were dominant in 71.3% of the women, followed by Gardnerella (17.4%), Streptococcus (8.7%), and Enterococcus (2.2%). Of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
245
0
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(277 citation statements)
references
References 32 publications
(44 reference statements)
11
245
0
21
Order By: Relevance
“…produce both the D- and L-lactic acid isomers60. Witkin and colleagues (2013) recently reported elevated levels of D-lactic acid in vaginal microbiomes dominated by L. crispatus and showed that an increased ratio of D- to L-lactic acid promotes the expression of vaginal extracellular matrix metalloproteinase inducer, which in turn can activate matrix metalloproteinase-8 and may subsequently alter cervical integrity61. Such studies designed to improve understanding of the functional relevance of specific vaginal community state types during pregnancy could help clarify recent conflicting reports regarding the association of the vaginal microbiome in preterm birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…produce both the D- and L-lactic acid isomers60. Witkin and colleagues (2013) recently reported elevated levels of D-lactic acid in vaginal microbiomes dominated by L. crispatus and showed that an increased ratio of D- to L-lactic acid promotes the expression of vaginal extracellular matrix metalloproteinase inducer, which in turn can activate matrix metalloproteinase-8 and may subsequently alter cervical integrity61. Such studies designed to improve understanding of the functional relevance of specific vaginal community state types during pregnancy could help clarify recent conflicting reports regarding the association of the vaginal microbiome in preterm birth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al also observed that cervical microbiota clustered in six distinct community types, one of which was characterized by a predominance of L. iners (42) L. iners , discovered by Falsen et al (43) has escaped attention because it grows only on blood agar. L. iners -dominated samples have lower concentrations of D-lactic acid, which is protective against infection by pathogens (44). L. iners has also been reported to induce IL-8 secretion in vivo and thereby potentially moderate pro-inflammatory activity in the cervix which may influence CIN progression (36).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli use several mechanisms to inhibit colonization by other bacteria including pathogens. Vaginal epithelial cells produce glycogen, which lactobacilli ferment, producing D- and L- lactic acid 18 . Some species produce hydrogen peroxide in vitro; however, recent studies suggest that in the hypoxic conditions that exist in the vagina, concentrations may never achieve levels that are inhibitory to other bacteria 19 .…”
Section: Healthy Lactobacillus Dominated Vaginal Floramentioning
confidence: 99%